Walking On Embers: The Complexity of Adolescent Sexual Dynamics and Its Implications for Sex Education Structure in University - Pratama, Teguh Agum; al Mujahid, Naqil Sayyaf (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palu, 2025)
This article discusses the complexity of adolescent sexual behaviour in Indonesia and its implications for the need to reform sex education. The study highlights the increasing prevalence of premarital sex among adolescents, driven by uncontrolled access to sexual information via digital media. The urgency of this research lies in the lack of comprehensive sex education in Indonesia and the absence of open dialogue within families. This situation is exacerbated by the high number of adolescents engaging in premarital sex, with approximately 60% of those aged 16-17 involved. This study employs a qualitative approach using phenomenological methods to understand adolescents' perceptions and experiences of sexuality. Data were collected through content analysis of various digital platforms, including social media, news articles, videos, and online forums. This approach allows researchers to capture the nuances of how sexual information is disseminated and received by young audiences. Data triangulation techniques were employed to enhance the validity of the research by comparing multiple sources of information. Findings indicate that Indonesian adolescents are caught between traditional values and the influence of modernisation, particularly through social media. The wide accessibility of sexual information without proper guidance has led to confusion, risky sexual behaviour, increased teenage pregnancies, and the spread of sexually transmitted infections. This underscores the need for a more comprehensive reform of sex education in Indonesia, incorporating biological, psychological, social, and cultural dimensions. In conclusion, reforming sex education in Indonesia is crucial to providing adolescents with a more holistic understanding of sexuality in the digital age.